Consumer Beliefs and Attitudes towards Advertising Media:A Study of Indian Women - Dutta, Kirti (Indian Journal of Marketing, 2009)
Advertising is the most visible and noticeable component of the communication mix (Coulter, Zaltman and Coulter, 2001) but marketers, policy makers, academics and executives continue to debate its merits (Macias and Lewis, 2003). It has been evidenced that attitudes toward advertising in general is a major determinant of brand attitudes and purchase intentions (Mackenzie and Lutz, 1989, Ashill and Yavas, 2005). Thus, advertising has long been used to influence customers towards consuming brands and to develop perceptions of the consumers towards advertised brands thus influencing brand attitudes (Teng et al, 2007, Till and Baack, 2005). According to Smith and Swinyard's Integrated Information Response Model (1982) (cited in Smith and Swinyard, 1983), advertising as an information source affects product trial purchase and post trial advertising has a higher impact on information acceptance leading to repeat purchase (thus affecting both purchase decision and post purchase behavior).